106k views
5 votes
Evaluate -(3-6)(33).

User Mrsoltys
by
5.0k points

2 Answers

1 vote


\longrightarrow{\green{ 99 }}


\large\mathfrak{{\pmb{\underline{\red{Step-by-step\:explanation}}{\red{:}}}}}


- (3 - 6)(33)

=
\: - ( - 3)(33)

=
\: 3 * 33


(∵ - * - = + )

=
\: 99

Note:-


\sf\pink{PEMDAS\: rule.}

P = Parentheses

E = Exponents

M = Multiplication

D = Division

A = Addition

S = Subtraction


\large\mathfrak{{\pmb{\underline{\orange{Mystique35 }}{\orange{♨}}}}}

User Thell
by
4.9k points
3 votes

Answer:

99

Explanation:

-(3-6)(33)

(-3+6)(33)

(3)(33)

= 99

User Nikolas
by
4.5k points